Kajian Banding Secara Numerik Kapasitas dan Perilaku Balok Baja Kastela Menggunakan Program SAP 2000 - Suharjanto, Suharjanto (Department of Civil Engineering, Diponegoro University, 2005)
Extraordinary saving can be obtainef from an often forgotten design concept. The open-web expanded steel beam as usually call castellated steel beam has already paid substantial dividends for various engineering firm. It should be considerd and many more projects. The opening up of a rolled beam (I-section) increases its section modulus and moment inertia, result its greater strength and rigidity. The reduction in beam weight has a chain effect on saving throughout the structure. The result of numeric simulation using computer program SAP-2000 show that the load capacity of castellated steel increase 92,307% compared with its origin section, that is rolled beam or I sevtion steel beam. and the maximum deflection of castellated steel decrease 45.683% compared with its origin section, that is rolled beam or I section steel beam.Keywords : Casrellated, rolled beam, load capacity, deflectionPermalink: http://ejournal.undip.ac.id/index.php/mkts/article/view/3915[How to cite: Suharjanto, 2005, Kajian Banding Secara Numerik Kapasitas dan Perilaku Balok Baja Kastela Menggunakan Program SAP 2000, Jurnal Media Komunikasi Teknik Sipil, Volume 13, Nomor 2, pp. 114-121]